Differentiation of Composite Functions

Composite functions require the Chain Rule for differentiation. This method helps analyze nested functions in calculus.

Neetesh Kumar

Neetesh Kumar | February 08, 2025                                      \space \space \space \space \space \space \space \space \space \space \space \space \space \space \space \space \space \space \space \space \space \space \space \space \space \space \space \space \space \space \space \space \space \space \space \space \space Share this Page on: Reddit icon Discord icon Email icon WhatsApp icon Telegram icon


Table of Content:


Definition of Derivative of Composite Functions:

Derivative of Composite Functions:
If a function y=f(g(x))y = f\big(g(x)\big) is a composite function, where g(x)g(x) is the inner function and f(x)f(x) is the outer function, then the derivative of yy with respect to xx is given by:

dydx=f(g(x))g(x)\boxed{\frac{dy}{dx} = f'\big(g(x)\big) \cdot g'(x)}

This is known as the chain rule and is used to differentiate composite functions, where we differentiate the outer function with respect to the inner function, and then multiply by the derivative of the inner function.


Explanation & Intuition:

  • The derivative of composite functions is important when dealing with functions inside other functions, such as nested polynomials, exponentials, and trigonometric functions.
  • This rule allows us to break down complex differentiation problems by treating the inner and outer functions separately.
  • The rule is widely used in fields like calculus, physics, and economics, where nested relationships occur frequently.

Derivative Examples with Solutions:

Example 1: Differentiating a Polynomial Inside a Power Function

Differentiate f(x)=(3x2+2x)4f(x) = (3x^2 + 2x)^4.

Solution:

Using the chain rule, let:

  • Outer function: f(u)=u4f(u) = u^4, so f(u)=4u3f'(u) = 4u^3.
  • Inner function: g(x)=3x2+2xg(x) = 3x^2 + 2x, so g(x)=6x+2g'(x) = 6x + 2.

Applying the chain rule:

f(x)=4(3x2+2x)3(6x+2)f'(x) = 4(3x^2 + 2x)^3 \cdot (6x + 2)

Thus, the final answer is: 4.(3x2+2x)3.(6x+2)\boxed{4.(3x^2 + 2x)^3 .(6x + 2)}.


Example 2: Differentiating a Trigonometric Function Inside an Exponential

Differentiate f(x)=esin(x)f(x) = e^{\sin(x)}.

Solution:

Using the chain rule, let:

  • Outer function: f(u)=euf(u) = e^u, so f(u)=euf'(u) = e^u.
  • Inner function: g(x)=sin(x)g(x) = \sin(x), so g(x)=cos(x)g'(x) = \cos(x).

Applying the chain rule:

f(x)=esin(x)cos(x)f'(x) = e^{\sin(x)} \cdot \cos(x)

Thus, the final answer is: esin(x).cos(x)\boxed{e^{\sin(x)} .\cos(x)}.


Example 3: Differentiating a Logarithmic Function Inside a Polynomial

Differentiate f(x)=ln(5x3+3x+1)f(x) = \ln(5x^3 + 3x + 1).

Solution:

Using the chain rule, let:

  • Outer function: f(u)=ln(u)f(u) = \ln(u), so f(u)=1uf'(u) = \dfrac{1}{u}.
  • Inner function: g(x)=5x3+3x+1g(x) = 5x^3 + 3x + 1, so g(x)=15x2+3g'(x) = 15x^2 + 3.

Applying the chain rule:

f(x)=15x3+3x+1(15x2+3)f'(x) = \dfrac{1}{5x^3 + 3x + 1} \cdot (15x^2 + 3)

Thus, the final answer is: 15x2+35x3+3x+1\boxed{\frac{15x^2 + 3}{5x^3 + 3x + 1}}.


Example 4: Finding the Rate of Change of Velocity in Physics

The velocity v(t)v(t) of a particle is given by: v(t)=(3t2+1)5v(t) = (3t^2 + 1)^{5}.

Find the rate of change of velocity (i.e., acceleration) at time t=2t = 2.

Solution:

Using the chain rule, let:

  • Outer function: f(u)=u5f(u) = u^5, so f(u)=5u4f'(u) = 5u^4.
  • Inner function: g(t)=3t2+1g(t) = 3t^2 + 1, so g(t)=6tg'(t) = 6t.

Applying the chain rule:

a(t)=ddt(3t2+1)5=5(3t2+1)4(6t)a(t) = \dfrac{d}{dt} (3t^2 + 1)^5 = 5(3t^2 + 1)^4 \cdot (6t)

Substitute t=2t = 2:

a(2)=5(3(2)2+1)4(6(2))a(2) = 5(3(2)^2 + 1)^4 \cdot (6(2))

a(2)=5(12+1)412=5(13)412=1713660a(2) = 5(12 + 1)^4 \cdot 12 = 5(13)^4 \cdot 12 = 1713660

Thus, the acceleration at t=2t = 2 is: 1713660\boxed{1713660}.


Conclusion:

  • The derivative of composite functions using the chain rule is essential for differentiating nested functions.
  • It is widely used in calculus, especially in physics, engineering, and economics, for functions that involve compositions like polynomials inside exponentials or trigonometric functions.
  • By applying the chain rule, we can break down and differentiate complex functions effectively.